Metatranscriptome Analysis of the Vaginal Microbiota Reveals Potential Mechanisms for Protection against Metronidazole in Bacterial Vaginosis - Zhi-Luo Deng (American Society for Microbiology, 2018)
ABSTRACT Bacterial vaginosis (BV) is a prevalent multifactorial disease of women in their reproductive years characterized by a shift from the Lactobacillus species-dominated microbial community toward a taxonomically diverse anaerobic community. For unknown reasons, some women do not respond to therapy. In our recent clinical study, among 37 women diagnosed with BV, 31 were successfully treated with metronidazole, while 6 still had BV after treatment. To discover possible reasons for the lack of response in those patients, we performed a metatranscriptome analysis of their vaginal microbiota, comparing them to the patients who responded. Seven of 8 clustered regularly interspaced short palindromic repeat (CRISPR)-associated (Cas) genes of Gardnerella vaginalis were highly upregulated in nonresponding patients. Cas genes, in addition to protecting against phages, might be involved in DNA repair, thus mitigating the bactericidal effect of DNA-damaging agents such as metronidazole. In the second part of our study, we analyzed the vaginal metatranscriptomes of four patients over 3 months and showed high in vivo expression of genes for pore-forming toxins in L. iners and of genes encoding enzymes for the production of hydrogen peroxide and d-lactate in L. crispatus. IMPORTANCE Bacterial vaginosis is a serious issue for women in their reproductive years. Although it can usually be cured by antibiotics, the recurrence rate is very high, and some women do not respond to antibiotic therapy. The reasons for that are not known. Therefore, we undertook a study to detect the activity of the complete microbiota in the vaginal fluid of women who responded to antibiotic therapy and compared it to the activity of the microbiota in women who did not respond. We found that one of the most important pathogens in bacterial vaginosis, Gardnerella vaginalis, has activated genes that can repair the DNA damage caused by the antibiotic in those women that do not respond to therapy. Suppressing these genes might be a possibility to improve the antibiotic therapy of bacterial vaginosis.